2018
DOI: 10.4236/ce.2018.912134
|View full text |Cite
|
Sign up to set email alerts
|

Kindergarten Teachers’ Beliefs about the Relationship between Music and Early Learning

Abstract: Music has been shown to be positively related to early learning and academic outcomes. Teachers' beliefs about how children learn and how they think about their own skills and competencies have also been shown to be linked to educational outcomes. The purpose of the present study was to examine kindergarten teachers' beliefs about the role of music in the curriculum and its relationship to classroom learning and educational outcomes. The methods involved surveying two teachers, one a classroom teacher, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…One would therefore assume that singing is an obvious part of everyday life in all ECEC settings. However, mounting evidence suggests that ECEC staff have a considerable lack of confidence in their music-making skills (Barrett et al 2019;Barrett, Flynn, and Welch 2018;Ehrlin 2014;Ehrlin and Tivenius 2018;Ehrlin and Wallerstedt 2014;Flores 2018;Hallam et al 2009;Kim and Kemple 2011;Kulset 2016b;Nardo et al 2006;Russell-Bowie 2009;Stunell 2010;Swain and Bodkin-Allen 2014;Welch and Henley 2014). Barrett et al (2019) found that the more qualified the ECEC staff members were (that is, the more training they had as ECEC teachers), the less favourable their beliefs regarding the role of music in ECEC settings.…”
Section: Introductionmentioning
confidence: 99%
“…One would therefore assume that singing is an obvious part of everyday life in all ECEC settings. However, mounting evidence suggests that ECEC staff have a considerable lack of confidence in their music-making skills (Barrett et al 2019;Barrett, Flynn, and Welch 2018;Ehrlin 2014;Ehrlin and Tivenius 2018;Ehrlin and Wallerstedt 2014;Flores 2018;Hallam et al 2009;Kim and Kemple 2011;Kulset 2016b;Nardo et al 2006;Russell-Bowie 2009;Stunell 2010;Swain and Bodkin-Allen 2014;Welch and Henley 2014). Barrett et al (2019) found that the more qualified the ECEC staff members were (that is, the more training they had as ECEC teachers), the less favourable their beliefs regarding the role of music in ECEC settings.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the development of gross and fine mobility, by majority both, general and special Kindergarten teachers evaluated the use of graded difficulty materials by the pupils, as very important (Anagnostopoulou, 2017). The learning domain of Arts holds a prominent place within the Kindergarten curriculum, according to the participants, since most of them consider that the engagement of children with artistic activities is very important, while, at the same time, music comprises an inextricable part of the activities (Flore, 2018;Papadogianni-Kouranti & Anagnostopoulou, 2019;Sullivan, 2016). During the assessment of dramatic play, a division was observed among the educationalists, half of which stated that there is no organised interest spot regarding drama play in their classroom, while as incomplete were described the materials available for disguise, which, in addition, fail to promote the concept of diversity.…”
Section: Discussion Of the Conclusionmentioning
confidence: 99%
“…In prior interview studies, ECE teachers highlighted the importance of their own role as facilitators of quality music education, predominately focusing on how teachers should prepare, design, and implement musical activities in ECE classrooms [7,8]. For example, in an interview study conducted in the United States by Flores [9], kindergarten teachers suggested quality teaching examples to integrate music with other learning areas. Participants recommended designing musical activities such as singing songs in different languages to expose children to foreign languages, and drawing/making an instrument to promote children's musical creativity and expression.…”
Section: Perspectives and Practices On Ece Music Education Around The...mentioning
confidence: 99%